A study on the impact of Artificial Intelligence (AI), automation and the digital transformation on society - Gohil , Manish G. (Revista Review Index Journal of Multidisciplinary, 2023)
This study delves into the intricate and multifaceted impact of Artificial Intelligence (AI), automation, and digital transformation on contemporary society. Through a comprehensive analysis of existing literature, technological landscapes, and real-world case studies, the research aims to illuminate the transformative effects of these technologies on various aspects of societal structures. The investigation encompasses economic shifts, changes in employment patterns, ethical considerations, and the evolving cultural landscape influenced by AI and automation. Additionally, the study explores the legal and regulatory frameworks governing these technologies, providing insights into the challenges and opportunities they present. The findings contribute to a deeper understanding of the complex interplay between technological advancements and societal dynamics, offering valuable implications for policymakers, industries, and the broader community.